GRUA Gentlemen de Rua: modes of production and communication of a creation process in times of crisis - Miranda Dias, Wagner; Almeida Salles, Cecilia (Revista Brasileira de Estudos da Presença, 2023)
This article examines communicative practices and modes of production in the creation process of the dance and performance group GRUA Gentlemen de Rua, in the period of the 2020 crisis, observing creative procedures that intersect with audiovisual media and the use of cyberspace, investigating whether these relationships are characterized as actions of resistance and reinvention. For this, we discuss documents generated by the Group, such as projects, notes, scripts, films, websites, etc. The theoretical foundation is structured from the critical theory of creation processes by Cecilia Almeida Salles and proposes dialogues with Edgar Morin, Pierre Musso, Zygmunt Bauman, Josette Féral and Vincent Colapietro, among others.